Selected Problems of African Agriculture and Food Production - Kiss Lívia Benita (Zagadnienia Ekonomiki Rolnej)
Agriculture is the dominant economic sector in Africa. Africa is distinguished by a large population working in agriculture, abundant and fertile land for self-sufficient food production, and even surplus production. However, the growth rate of food production and the ratio of those employed in agriculture to the total workforce clearly reflect the poor state of the sector. The main objective of the study is to identify the main problems and obstacles that have contributed to the underdevelopment of African agriculture from the 2010s to 2022, and to find solutions to them. The most determining factors of the continent’s agriculture were collected using a PESTEL analysis. Using problem tree analysis, this paper examines the obstacles and problems that hinder the development of agriculture in Africa. It seeks answers to the problems that African governments and farmers should find solutions to in order to safely supply food to the ever-growing population. As a result, a solution tree was created. The development and modernization of agriculture in Africa is absolutely necessary to pave the way for food security and economic recovery. Self-sufficient food production would be the goal, taking into account sustainable development, which would require the identification of key policy areas, education and grassroots development of the sector, as well as curbing corruption and targeting subsidies.